Validation of the Palliative Prognostic Score (PaP score) in Patients with Metastatic Cancers in Dr. Sardjito General Hospital Yogyakarta - Prafita Cahya Dewanti; Johan Kurnianda; Kartika Widayati (Faculty of Medicine Universitas Gadjah Mada, 2019)
Background. The mortality burden of cancer continues to increase in developing countries, most likely because of a late-stage at diagnosis. Identify the terminal stage is important in patients with advanced cancer because no longer aggressive therapy in patients with terminal cancer. Palliative prognostic score (PaP score)is a scoring system to predict the probability of survival within 30 days in patients with advanced cancer. PaP score divided into the heterogeneous patient sample into three iso-prognostic groups related to the chance of 30-days survival. Group A, score: 0 to 5.5 (the probability of survival within 30 days > 70%); Group B, score: 6-11 (the probability of survival in 30 days 30-70%) and group C, the score: 11.5 to 17.5 (the probability of survival in 30 days <30%).Aims. The aim of this study was to validate and to evaluate the prognostic accuracy of the palliative prognostic (PaP score) to predict 30-days survival in patients with metastatic cancers in Dr. Sardjito General Hospital Yogyakarta.Methods. The design of this prognostic study was cohort, including patients with metastatic cancers who were visited in Tulip Hematology and Medical Oncology Clinic, inpatient and outpatient care in Dr. Sardjito General hospital during May 2015 until May 2016. The PaP score calculated in 159 consecutive patients with metastatic cancers. The positive predictive value of the PaP score was evaluated and survival analysis was performed to compare the survival of the three prognostic groups.Results. PaP score tested on 159 subjects with overall median survival was 90 days, 76 subjects categorized into group A, 22 subjects into group B and 61 patients into group C. The 30-day survival probability was 98.7% for group A (median survival could not be assessed), 63.6 % probability of 30-day survival for the group B with median survival was 35 days and for group C with 3.3% probability of 30-day and median survival was 6 days. These survival differences were highly significant (log-rank test of trends, X =203.97; P<0.0001).The positive predictive value of the PaP score in predicting 30-day mortality was 96.7% with an accuracy of PaP the score was 93.1%.Conclusion. PaP score was a valid test tool in determining prognosis in patients with metastatic cancers with high accuracy and precision in predicting 30-days survival.Keywords: PaP score, validation, survival, prognostic, metastatic cancers.